Altered colonic motility is associated with low anterior resection syndrome. (14th December 2020) - Keane, Celia; Paskaranandavadivel, Nira; Vather, Ryash; Rowbotham, David; Arkwright, John; Dinning, Phil; Bissett, Ian; O'Grady, Greg
Abstract: Aim: Patients frequently suffer from low anterior resection syndrome (LARS) after distal colorectal resection. The pathophysiology of LARS has not been clearly elucidated. We hypothesized that rectosigmoid resection could impair motility patterns in the distal colon, such as the rectosigmoid brake, which contribute to control of stool form and frequency. Method: High‐resolution colonic manometry was performed in patients who had previously undergone distal colorectal resection (mean 6.8 years after resection) and non‐operative controls before and after a standardized meal. Symptoms were assessed using the LARS score. Propagating contractions were compared between patients with and without LARS, and controls. Results: Data were analysed from 23 patients (11 no‐LARS; 12 LARS) and nine controls. All groups demonstrated a significant meal response. LARS patients had fewer post‐prandial antegrade propagating contractions than controls ( P  = 0.028), and fewer retrograde propagating contractions both pre‐ ( P  = 0.005) and post‐prandially ( P  = 0.004). Post‐prandially, the LARS group had a significantly lower percentage of propagating contractions that met the criteria for the cyclic motor pattern compared to the control group (26% vs. 58%; P  = 0.009). There were significant differences in antegrade and retrograde amplitude ( P  = 0.049; P  = 0.018) and distance of propagation ( P  = 0.003; P  = 0.002) post‐prandially between LARS patients and controls. Conclusion: Rectosigmoid resection alters the meal response following anterior resection, including impairment of the rectosigmoid brake cyclic motor pattern. These findings help to quantify the impaired functional motility after rectosigmoid resection and offer new insights into the mechanisms of LARS.